FoMO Scale: A Measuring Tool to Analyse the Fear of Missing Out Moments from Others in Adolescents in Indonesia - Agus Supriyanto; Mungin Eddy Wibowo; Mulawarman Mulawarman; Muhammad Japar (International Conference on Science, Education, and Technology, 2022)
Technological developments create extraordinary social media access. Teenagers, most social media users, make them vulnerable to FOMO. FOMO (Fear of Missing Out) is a feeling of worry and anxiety teenagers feel when they miss moments on social media. The goal is to find a valid and reliable FoMO scale instrument for Indonesian adolescents. The research model is a mix-method with qualitative data through interviews and literature studies to see the relevant instrument grid. The test subjects were 77 adolescents with an average age of 19-20 years—the data analysis with product moment and alpha-Cronbach. The conclusion of this study first found the existence of FoMO among adolescent social media users. Qualitative data found a lattice of instruments with aspects of FoMO on social media from a) not being able to stay away from cellphones, b) frequently checking social media to find out what friends have uploaded, and c) feeling uncomfortable when not attending gatherings and sharing information with friends, and d) often evoke social media status related to their activities. Second, the most significant cause of FoMO is social media and smartphones. The test of the validity and reliability of the scale instrument found that as many as 20 of the 24 FoMO statement items were valid with a reliability coefficient of 0.721, which was included in the high category. All researchers, with the emergence of various prevention, alleviation strategies, psychoeducational activities, guidance and counselling, can apply the FoMO scale for social media.